Bitcoin, gold and the dollar: A GARCH volatility analysis - Anne Haubo Dyhrberg (University College Dublin, UCD School of Economics, 2015)
This paper explores the financial asset capabilities of bitcoin using GARCH models. The initial model showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange. The asymmetric GARCH showed that bitcoin may be useful in risk management and ideal for risk averse investors in anticipation of negative shocks to the market. Overall bitcoin has a place on the financial markets and in portfolio management as it can be classified as something in between gold and the American dollar on a scale from pure medium of exchange advantages to pure store of value advantages.
Keywords: 330; Bitcoin; GARCH; Volatility